2024
DOI: 10.1101/2024.02.01.575742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogenesis of cytochromescandc1in the electron transport chain of malaria parasites

Aldo E. García-Guerrero,
Rebecca G. Marvin,
Amanda Mixon Blackwell
et al.

Abstract: Plasmodiummalaria parasites retain an essential mitochondrional electron transport chain (ETC) that is critical for growth within humans and mosquitoes and a key antimalarial drug target. ETC function requires cytrochromes c and c1that are unusual among heme proteins due to their covalent binding to heme via conserved CXXCH sequence motifs. Heme attachment to these proteins requires the mitochondrial enzyme holocytochrome c synthase (HCCS) that binds heme and the apo cytochrome to facilitate biogenesis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
1
0
1
Order By: Relevance
“…2A). This rapid sensitivity differs from our prior knockdown studies of proteins localized to the apicoplast and mitochondrion, in which growth phenotypes were not observed until at least the second cycle of RBC infection 12, 48, 49, 75 . The unusual sensitivity of parasites to PfDMT1 knockdown may reflect the need to fully synthesize this protein de novo in each life cycle, since the FV is not inherited by daughter parasites (unlike the apicoplast and mitochondrion).…”
Section: Discussioncontrasting
confidence: 85%
“…2A). This rapid sensitivity differs from our prior knockdown studies of proteins localized to the apicoplast and mitochondrion, in which growth phenotypes were not observed until at least the second cycle of RBC infection 12, 48, 49, 75 . The unusual sensitivity of parasites to PfDMT1 knockdown may reflect the need to fully synthesize this protein de novo in each life cycle, since the FV is not inherited by daughter parasites (unlike the apicoplast and mitochondrion).…”
Section: Discussioncontrasting
confidence: 85%
“…Critically, we observed that growth in -aTC conditions reduced PfHO levels by >85% (Figure 3C), indicating substantial downregulation of PfHO protein expression. PfHO mRNA levels were also selectively decreased by ~75% upon aTC washout, consistent with prior reports that TetR-DOZI association with transcripts targets mRNA to P-bodies for degradation (Figure 3 -figure supplement 6) [48][49][50] . Because of the consistency and stringency of knockdown achieved by the PfHO-aptamer/TetR-DOZI system, all subsequent knockdown experiments were performed in this line.…”
Section: Figure Supplement 1 Sequence Homologs Of Pfho Based On Blastsupporting
confidence: 89%